Pengaruh Self-Efficacy dan Self-Esteem terhadap akuntabilitas pengelolaan dana Desa dengan Sistem Pengendalian Internal sebagai variable moderasi - Leiwakabessy, Theophilia F.F.; Usmany, Alfrin E.M; Limba, Franco B. (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to empirically examine the effect of self-efficacy and self-esteem possessed by village officials on village fund management’s accountability by using the Internal Control System as a moderating variable. The population in this study were village officials in the Negeri Adat in Ambon, with a sample of 71 people. The sampling technique used is saturated sampling. The data analysis method used is multiple regression to test the effect of self-efficacy and self-esteem variables on village fund management’s accountability, and using MRA to test the role of the Internal Control System as a moderating variable. The results of this study are self-efficacy and self-esteem affect the accountability of village fund management. While the Internal Control System does not act as a moderating variable, but as a Predictor Variable Moderation.